Analysis of Local Culture in English Learning Material in Junior High School - Fadhillah, Yuyun; Alifa, Yumna (Universitas Serambi Mekkah, 2024)
This research aims to analyze the extent to which local cultural elements are integrated into English language learning materials for junior high school. The focus of this study is on the English language book